STRATEGI KOMUNIKASI INTERNAL PT REGENE ARTIFISIAL INTELIGEN DALAM MEMINIMALISIR KONFLIK ANTAR GENERASI - Sarah Aprilia Haris; Gita Widiasanty (ADISAM PUBLISHER, 2026)
Intergenerational conflict presents a critical challenge at PT Regene Artifisial Inteligen, a genomics-based biotechnology startup focusing on precision health services, with a predominantly Generation Z workforce. Fundamental differences in perspectives on work ethic, working hours, expectations of responsiveness outside office hours, and work-life balance frequently trigger tensions. These directly impact operations, leading to issues such as delays in uploading marketing content or underperforming advertising campaigns, which risk hindering the achievement of sales targets. This qualitative study deeply investigates the company's internal communication strategies aimed at minimizing such friction. Through in-depth interviews with management, including the General Manager as a key informant, and employees across generations (Baby Boomers, Gen X, Gen Y, and Gen Z), it was revealed that no effective formal system or dedicated platform is in place to address these dynamics. Conflict resolution tends to be informal through direct communication, reactive, reliant on individual initiatives, and persuasive leadership approaches in routine meetings. Significant perceptual gaps and intergenerational stereotypes persist, indicating that communication objectives to secure understanding, establish acceptance, and motivate action have not been optimally achieved. The absence of a well-established HRD division was also highlighted. This study underscores that reliance on informal mechanisms is insufficient. Therefore, PT Regene Artifisial Inteligen is strongly advised to design and implement a comprehensive, structured, proactive, and adaptive internal communication strategy. This includes establishing participatory two-way dialogue channels, strengthening the HRD function, and programs explicitly designed to bridge generational differences, thereby fostering a harmonious and collaborative work environment.